Sistem Pendukung Keputusan Produksi Pada PT. Maitland Smith Indonesia (Information Technology and Telematics, 2013)
Nowadays the decision making also requires information technology, this is due to the presence of the globalization era requires a company to move fast in taking a decision and action, if not then these  companies will compete with other companies. As with any other company, PT. Maitland Smith Indonesia also require someone who can decision makers take decisions rapidly and precisely in the process of scheduling the production of furniture. The purpose will be achieved is to produce a production decision support system PT. Maitland Smith Indonesia which can determine the furniture production PT. Maitland Smith Indonesia. The result in this study is a decision support system that is created can support PT. Maitland Smith  Indonesia in knowing production schedule so that it doesn’t happen the same schedule in the production process.     Keywords   Sistem Pendukung Keputusan, Produksi, PT. Maitland Smith Indonesia